2012
DOI: 10.4172/jcmhe.1000133
|View full text |Cite
|
Sign up to set email alerts
|

Kindergarten Readiness and Performance of Latino Children Participating in Reach out and Read

Abstract: Background: Literacy is a vital skill that forms the basis for academic, occupational, and social success. Minority populations, especially immigrant Latinos in the US, have achievement gaps in literacy when compared to the White population. The Reach Out and Read (ROR) program is a pediatric, primary-care intervention designed to promote emergent literacy skills. The objectives of this study were to provide descriptive information at kindergarten on Latino immigrant children's emergent literacy skills and hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
5
0
1
Order By: Relevance
“…suggests that reading together around a blended use of digital and nondigital resources have the potential to increase oral language skills between parents and children. Parent-child reading routines on a daily basis have been documented to enhance emergent literacy skills as promoted by the national program called Reach Out and Read, endorsed by the American Academy of Pediatrics (Diener, Hobson-Rohrer, & Byington, 2012). Parents who participated in the Reach Out and Read program, which encourages reading books aloud to children every day, were more likely to report that reading was a favorite activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…suggests that reading together around a blended use of digital and nondigital resources have the potential to increase oral language skills between parents and children. Parent-child reading routines on a daily basis have been documented to enhance emergent literacy skills as promoted by the national program called Reach Out and Read, endorsed by the American Academy of Pediatrics (Diener, Hobson-Rohrer, & Byington, 2012). Parents who participated in the Reach Out and Read program, which encourages reading books aloud to children every day, were more likely to report that reading was a favorite activity.…”
Section: Discussionmentioning
confidence: 99%
“…A third limitation of the study is that, while many race ethnicities were represented in the study, minorities made up a smaller proportion of those surveyed. Several studies have demonstrated that "parent-child joint book reading is sensitive to the cultural background of the family" (Bus, Leseman, & Keultjes, 2000;Diener, Hobson-Rohrer, & Byington, 2012 could be used to design even more oral health literacy curricula in the future that are skill-based and inclusive to goal setting, decision making, and communication.…”
Section: Limitationsmentioning
confidence: 99%
“…A substantial evidence base has shown that parents whose children receive primary care at ROR participating sites are likelier to share books, to have reading materials at home, and to describe reading aloud as a regular activity [46]. A longitudinal analysis of Latino CIF whose parents were engaged with ROR from the time of the first well-child visit were found to have greater phonemic awareness and familiarity with print at the time of kindergarten entry [47]. Despite risk factors for poor academic achievement, most of these children were determined to be average or above average in reading proficiency by the completion of kindergarten.…”
Section: Promotion Of School Readiness In the Household Setting: Agesmentioning
confidence: 97%
“…9 More recent studies on the effects of pediatric literacy promotion have also shown improvements not just in reading proficiency but also childhood vocabulary, readiness to enter elementary school, and communication skills. 10,11 Existing literacy outreach programs have demonstrated significant benefits apart from just improving childhood literacy. Book distribution by programs like Reach Out and Read and other initiatives have been shown to increase the likelihood of adult caregivers utilizing public libraries for reading materials as well as other community resources.…”
Section: Lessons Learnedmentioning
confidence: 99%